Autonomic Regulation of the Goldfish Intact Heart - Bazmi, Maedeh; Escobar, Ariel L. (Frontiers in Physiology, 2022)
Autonomic regulation plays a central role in cardiac contractility and excitability in numerous vertebrate species. However, the role of autonomic regulation is less understood in fish physiology. Here, we used Goldfish as a model to explore the role of autonomic regulation. A transmural electrocardiogram recording showed perfusion of the Goldfish heart with isoproterenol increased spontaneous heart rate, while perfusion with carbamylcholine decreased spontaneous heart rate. Action potentials measured with sharp microelectrodes mirrored these electrocardiographic results, as the spontaneous heart rate was observed to either increase or decrease the following perfusion with isoproterenol or carbamylcholine, respectively. Sharp microelectrode recordings also showed perfusion with isoproterenol shortened the action potential duration, while perfusion with carbamylcholine lengthened the action potential duration. To evaluate cardiac contractility, the Goldfish heart was perfused with the Ca2+ indicator Rhod-2 and ventricular epicardial Ca2+ transients were measured using Pulsed Local Field Fluorescence Microscopy. Following isoproterenol perfusion, the amplitude of the Ca2+ transient significantly increased, the half duration of the Ca2+ transient shortened, and there was an observable increase in the velocity of the rise time and fall time of the Ca2+ transient; all of which are compatible with the shortening of the action potential induced by isoproterenol perfusion. On the other hand, carbamylcholine perfusion significantly reduced the amplitude of the Ca2+ transient, shortened the rise time and increased the half duration of the Ca2+ transient. These results are interesting because the effect of carbamylcholine is opposite to what happens in classically used models, such as mouse hearts, and the autonomic regulation of the Goldfish heart is strikingly similar to what has been observed in larger mammalian models resembling humans.